2004
DOI: 10.1086/381928
|View full text |Cite
|
Sign up to set email alerts
|

HD 207651: A Triple System with Scuti and Ellipsoidal Variations But No Doradus Pulsations

Abstract: We examine HD 207651 as a possible example of a star exhibiting both Doradus and Scuti type pulsations. We find photometric periods of 0.06479 and 0.06337 days with peak-to-peak amplitudes in Johnson B of 21 and 13 mmag, respectively, clearly indicating Scuti pulsations. Additional light variation with a period of 0.73540 days and an even larger amplitude of 31 mmag is within the range of Doradus pulsation periods but results instead from the ellipticity effect. HD 207651 has a composite spectrum with a weak, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…demonstrated that the observed location of the Doradus variables agrees well with the theoretical instability strip of Warner et al (2003). Since the Doradus and the Scuti instability strips overlap, Henry et al (2004) continued the efforts of Handler & Shobbrook (2002) to find examples of stars pulsating intrinsically with both Doradus and Scuti frequencies. They concluded that the growing number of confirmed Doradus variables that also lie within the Scuti instability strip but do not exhibit additional Scuti variability makes it unlikely that the two types of pulsation can coexist in the same star.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…demonstrated that the observed location of the Doradus variables agrees well with the theoretical instability strip of Warner et al (2003). Since the Doradus and the Scuti instability strips overlap, Henry et al (2004) continued the efforts of Handler & Shobbrook (2002) to find examples of stars pulsating intrinsically with both Doradus and Scuti frequencies. They concluded that the growing number of confirmed Doradus variables that also lie within the Scuti instability strip but do not exhibit additional Scuti variability makes it unlikely that the two types of pulsation can coexist in the same star.…”
Section: Introductionmentioning
confidence: 54%
“…This work continues a series of papers in which we have examined the spectroscopic and photometric characteristics of candidate Doradus stars (most recently, , 2005Henry et al 2004). Early summaries of this new class of variable stars can be found in Kaye et al (1999a) and .…”
Section: Introductionmentioning
confidence: 62%
“…In several studies, V1464 Aql was classified as a spectroscopic binary system, RR Lyr (RRc), an eclipsing binary, possibly contact (EC) or semi-detached system (ESD) (Duerbeck 1997;Pourbaix et al 2004;Pribulla & Rucinski 2006; PASA, 30, e016 (2013) doi:10.1017/pasa.2012.016 Aerts et al (2002). c Henry et al (2004). d Chapellier et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…But Henry et al (2004) found that a long-term period component of HD 207651, 1.3598 cycle day À1 = 0.73540 days, did not result from a Doradus type term but from the ellipticity effect. From the spectroscopic observations an eclipsing period was twice the long-term period seen in the photometry.…”
Section: Singg Le-radial Mode Sx Phoenicis Stars With Longg -Term Varmentioning
confidence: 93%